Peran Pastoral dalam Mendorong Kualitas Hidup yang Berarti Bagi Lansia - Venidora Palbeno; Intan Pius Sakti X (International Forum of Researchers and Lecturers, 2024)
Elderly Catholics are an important part of the church community who require special attention as they face physical health challenges, emotional needs, and spiritual aspects that require special care. This article discusses the role of pastoral care in dealing with these challenges by promoting a meaningful quality of life for Catholic elderly. The method used in discussing this topic is a literature study. The pastoral role in encouraging the quality of life of elderly Catholics includes spiritual assistance, moral guidance, community services, counseling and emotional support, as well as education and coaching. Through this holistic approach, Catholic elderly can feel God's love and community support both physically and spiritually so that Catholic elderly live a more meaningful life.